Mutant Escherichia coli Ada proteins simultaneously defective in the repair of O6-methylguanine and in gene activation. - Demple, B (1986)
The activated Ada protein triggers expression of DNA repair genes in Escherichia coli in response to alkylation damage. Ada also possesses two distinct suicide alkyltransferase activities, for O6-alkylguanines and for alkyl phosphotriesters in DNA. The mutant Ada3 and Ada5 transferases repair O6-methylguanine in DNA 20 and 3000 times more slowly, respectively, than the wild-type Ada protein, but both exhibit normal DNA phosphotriester repair. These same proteins also exhibit delayed and sluggish induction of the ada and alkA genes. Since the C-terminal O6-methylguanine methyltransferase domain of Ada is not implicated in the direct binding of specific DNA sequences, this part of the Ada protein is likely to play an alternative mechanistic role in gene activation, either by promoting Ada dimerization, or via direct contacts with RNA polymerase.